All-Okinawa Council’s Transnational Advocacy Network Strategy: in Response towards the United States’ Military Base Construction in Okinawa - Putro, Annaas Satria Soesilo; Hidayatullah, Nur Luthfi (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
This research seeks to describe All-Okinawa Council’s transnational advocacy network strategy in response towards the United States’ military base construction in Henoko, Okinawa. This research utilizes descriptive qualitative method, with documentation data collection technique. The results of this research found that there are four strategies conducted by All-Okinawa Council, as a non-governmental organization in opposing the United States’ military base construction in Okinawa. Firstly, information politics by strengthening communication networks with mass media, government, and international non-governmental organizations. Secondly, symbolic politics by forming alliances with other advocacy groups with similar goals. Thirdly, leverage politics by organizing direct action campaigns and demonstrations to gain public attention and increase political pressure. Finally, accountability politics by holding meetings and discussions with political leaders and diplomatic representatives from the involved countries. This research concludes that All-Okinawa Council’s transnational advocacy network strategy has successfully influenced public opinion, obtained international support, and increased political pressure on the Japanese and American governments.